2007
DOI: 10.1128/mcb.00290-07
|View full text |Cite
|
Sign up to set email alerts
|

TOR Signaling Is a Determinant of Cell Survival in Response to DNA Damage

Abstract: The conserved TOR (target of rapamycin) kinase is part of a TORC1 complex that regulates cellular responses to environmental stress, such as amino acid starvation and hypoxia. Dysregulation of Akt-TOR signaling has also been linked to the genesis of cancer, and thus, this pathway presents potential targets for cancer chemotherapeutics. Here we report that rapamycin-sensitive TORC1 signaling is required for the S-phase progression and viability of yeast cells in response to genotoxic stress. In the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 48 publications
4
77
3
1
Order By: Relevance
“…Previously, Rnr3, another subunit of RNR has been implicated in MMS-induced mutation. Specifically, the inhibition of the TORC1 pathway, which controls transcription of RNR3 via Rad53, also results in a reduction of mutation in response to MMS [49]. These data suggest that the effect on induced mutation may be generalized to other subunits of the RNR complex.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 69%
“…Previously, Rnr3, another subunit of RNR has been implicated in MMS-induced mutation. Specifically, the inhibition of the TORC1 pathway, which controls transcription of RNR3 via Rad53, also results in a reduction of mutation in response to MMS [49]. These data suggest that the effect on induced mutation may be generalized to other subunits of the RNR complex.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 69%
“…Anti-apoptotic Bcl-2 and FLIPs, which were up-regulated in the transition from two-dimensional to three-dimensional, were found to be independent of mTOR/ S6K activity, suggesting that they may account for resistance that is not controlled by mTOR/S6K, at least in two of the cell lines. mTOR may also contribute to survival in general by its support of metabolism and energy (56) or of protein translation, key functions to which the cells may become reliant or "addicted" (58).…”
Section: Discussionmentioning
confidence: 99%
“…8). mTOR has also been shown to associate with mitochondria (55) possibly serving as a modulator of stress signals (56) and cell fate (57). Although we were able to localize the resistance to the mitochondria, we were not able to identify a specific molecule that transduced the survival function of mTOR/S6K in spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…The protein levels and activity of RNR are tightly controlled in all organisms because higher than physiological levels of dNTPs lead to gene mutations and lower levels compromise cell viability [40][41][42]. It was reported that rapamycin inhibition of TORC1 enhanced the cytotoxicity of DNA damage agents and at the same time reduced the DNA damage-induced mutations through downregulation of RNR in budding yeast, suggesting that the TOR pathway and DNA damage checkpoint function in parallel to control RNR in response to genotoxin [43]. The DNA damage-induced increase of dNTP levels is conserved in mammalian cells as one of the small subunits of mammalian RNR, p53R2, is induced by p53 following DNA damage [44].…”
Section: Tor Sustains Ribonucleotide Reductase In Response To Dna Damagementioning
confidence: 99%